THE PRACTICE OF PHYSICAL ACTIVITY AND THE USE OF CHATGPT AS A COUNSELING TOOL A PRÁTICA DE ATIVIDADE FÍSICA E O USO DO CHATGPT COMO UMA FERRAMENTA DE ACONSELHAMENTO - Sandreschi P.F. (2024)
© 2024, Sociedade de Estudos e Pesquisa Qualitativos. All rights reserved.This study analyzed ChatGPT's responses when questioned about physical activity recommendations for health based on the characteristics of users served by the Primary Health Care in the Brazilian Unified Health System (SUS). A simulation was conducted with an SUS user seeking information about physical activity for themselves and their family. The responses provided by ChatGPT were analyzed by a committee of experts and classified according to their alignment with global and national (Brazilian) physical activity guidelines. As a result, the responses were moderately satisfactory, with 23.1% of responses considered misaligned with information from reference documents, 46.2% moderately aligned, and 30.7% highly aligned. As more information becomes available regarding the formulation of responses provided by ChatGPT, the tool may assist in advising on public health physical activity.